DWT and IDWT Using Secret Key and Watermarking with in Video Compression - SHOBA, G.; JEYALAKSHMY, G. (IJRDO -Journal of Computer Science Engineering, 2016)
In this paper, Authenticating watermarking is nothing but inserting a hidden object in order to detect deceitful alteration by hackers. The object may be in terms of a secret key or password etc. There are quite few numbers of authentication methods are available for videos. Resent developers in digital video and internet technology helps the common user to easily produce illegal copies of videos. In order to solve the copyright protection problem and deceitful alteration by hackers of videos, several watermarking schemes have been widely used. Very few authenticating of watermarking schemes have been produced for defining the copyrights of digital video. The process of Digital watermark embeds the data called watermark in digital media like image, video, audio file etc. so that it can be claimed for rights. The paper represents the complete software implementation of 3-Level DWT algorithms and to have more secure data a secret key is used. The secret key is given to watermark image during embedding process and while extracting the watermark image the same secret key is used. To check effectiveness of the watermark video MSE and PSNR parameters are used.